2019
DOI: 10.1523/jneurosci.1376-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Zika Virus Infection in the Developing Mouse Produces Dramatically Different Neuropathology Dependent on Viral Strain

Abstract: Zika virus (ZIKV) infection during pregnancy has been causally linked to a constellation of neurodevelopmental deformities in the fetus resulting in a disease termed congenital Zika syndrome (CZS). Here we detail how ZIKV infection produces extensive neuropathology in the developing mouse brain and spinal cord of both sexes. Surprisingly, neuropathology differs depending on viral strain with a French Polynesian isolate producing primarily excitotoxicity and a Brazilian isolate being almost exclusively apoptoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 61 publications
2
19
0
Order By: Relevance
“…Animal models of postnatal ZIKV infection have the potential to be highly informative, considering the paucity of studies in children. Postnatally ZIKV-infected neonatal mice demonstrate extensive apoptotic degeneration in several brain regions, including the hippocampus, with activation being followed by the fragmentation of the microglia [ 67 ]. Impairments in motor and cognitive functions were also found in mice infected with ZIKV postnatally [ 68 ].…”
Section: Preclinical Models Of Postnatal Zika Virus Infectionmentioning
confidence: 99%
“…Animal models of postnatal ZIKV infection have the potential to be highly informative, considering the paucity of studies in children. Postnatally ZIKV-infected neonatal mice demonstrate extensive apoptotic degeneration in several brain regions, including the hippocampus, with activation being followed by the fragmentation of the microglia [ 67 ]. Impairments in motor and cognitive functions were also found in mice infected with ZIKV postnatally [ 68 ].…”
Section: Preclinical Models Of Postnatal Zika Virus Infectionmentioning
confidence: 99%
“…In the first model, Zika crosses the placenta barrier resulting in fetal infection and CNS damage and residual intrauterine growth, in more severe cases the infection resulted in fetal death, in the second case, after treatment with anti-interferon (IFN)-AB antibodies in the placenta, infection of the developing embryo occurred but was less severe and did not cause the death of the fetus. Furthermore, in Noguchi et al's 2019 [34] study, the effect of the Zika virus infection on the brain and the CNS of the mouse are presented-resulting in massive neurodegeneration of infected regions. The Brazilian Zika virus stain is also reported in the research and produces particularly devastating neuropathology in the fetal brain opposed to the viral French Polynesia stain.…”
Section: Resultsmentioning
confidence: 99%
“…No research had a score of 9 because all studies had a negative response to criterion5 (Table 1). [34] Notes: 1. Representative exposure sample, 2. selection of non-exposed, 3. exposure finding, 4. outcome did not precede the study, 5. adaptation for educational level, 6. adaptation for additional confounding factor, 7. outcome evaluation, 8. adequate monitoring time, 9. non-bias of wear.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies demonstrated that the African strain of ZIKV causes more severe infection, including in utero [ 55 , 56 ]. In vivo studies in which mice were infected with different strains of ZIKV also demonstrate variation in tissues tropism [ 57 ], neuropathology [ 58 ] and innate immune response [ 59 ]. Comparative studies with multiple strains of ZIKV are critical for defining genetic variation that may contribute to differences in immune response, pathology, and forward transmission potential.…”
Section: Discussionmentioning
confidence: 99%